Forensic Investigations in the Nuremberg Trials - A. Ya. Asnis; Sh. N. Khaziev (Теория и практика судебной экспертизы, 2016)
The authors present data on the forensic investigations conducted during the Nuremberg International Military Tribunal, as well as evaluation and use of expert testimony by the Tribunal, and characterize the main types of forensic investigations conducted both prior to the Tribunal and in the course of the trials. Certain procedural aspects of ordering and conducting forensic examinations are examined. The authors show how Nuremberg's forensic legacy provided an important contribution to the organization of forensic support for international and internationalized criminal courts and tribunals created in the post-1990s period.